Improving Our Ability to Predict Resident Applicant Performance: Validity Evidence for a Situational Judgment Test. Issue 5 (19th October 2020) - Cullen, Michael J.; Zhang, Charlene; Marcus-Blank, Brittany; Braman, Jonathan P.; Tiryaki, Ezgi; Konia, Mojca; Hunt, Matthew A.; Lee, Michael S.; Van Heest, Ann; Englander, Robert; Sackett, Paul R.; Andrews, John S.
Abstract: Construct: We investigated whether a situational judgment test (SJT) designed to measure professionalism in physicians predicts residents' performance on (a) Accreditation Council for Graduate Medical Education (ACGME) competencies and (b) a multisource professionalism assessment (MPA). Background: There is a consensus regarding the importance of assessing professionalism and interpersonal and communication skills in medical students, residents, and practicing physicians. Nonetheless, these noncognitive competencies are not well measured during medical education selection processes. One promising method for measuring these noncognitive competencies is the SJT. In a typical SJT, respondents are presented with written or video-based scenarios and asked to make choices from a set of alternative courses of action. Interpersonally oriented SJTs are commonly used for selection to medical schools in the United Kingdom and Belgium and for postgraduate selection of trainees to medical practice in Belgium, Singapore, Canada, and Australia. However, despite international evidence suggesting that SJTs are useful predictors of in-training performance, end-of-training performance, supervisory ratings of performance, and clinical skills licensing objective structured clinical examinations, the use of interpersonally oriented SJTs in residency settings in the United States has been infrequently investigated. The purpose of this study was to investigate whether residents' performance on an SJT designed to measure professionalism-related competencies—conscientiousness, integrity, accountability, aspiring to excellence, teamwork, stress tolerance, and patient-centered care—predicts both their current and future performance as residents on two important but conceptually distinct criteria: ACGME competencies and the MPA. Approach: We developed an SJT to measure seven dimensions of professionalism. During calendar year 2017, 21 residency programs from 2 institutions administered the SJT. We conducted analyses to determine the validity of SJT and USMLE scores in predicting milestone performance in ACGME core competency domains and the MPA in June 2017 and 3 months later in September 2017 for the MPA and 1 year later, in June 2018, for ACGME domains. Results: At both periods, the SJT score predicted overall ACGME milestone performance ( r = .13 and .17, respectively; p < .05) and MPA performance ( r = .19 and .21, respectively; p < .05). In addition, the SJT predicted ACGME patient care, systems-based practice, practice-based learning and improvement, interpersonal and communication skills, and professionalism competencies ( r = .16, .15, .15, .17, and .16, respectively; p < .05) 1 year later. The SJT score contributed incremental validity over USMLE scores in predicting overall ACGME milestone performance ( ΔR = .07) 1 year later and MPA performance ( ΔR = .05) 3 months later. Conclusions: SJTs show promise as a method for assessing noncognitive attributes in residency program applicants. The SJT's incremental validity to the USMLE series in this study underscores the importance of moving beyond these standardized tests to a more holistic review of candidates that includes both cognitive and noncognitive measures.